The use of social care services by individuals aged 50 and over diagnosed with colorectal cancer in Scotland: a linked data study. - Elizabeth Lemmon; Alasdair Rutherford; Peter Hall; David Bell; David Henderson; Amy Downing; Steve Clark (International Journal of Population Data Science, 2022)
The objective of this paper is to explore how a colorectal cancer (CRC) diagnosis influences an individual’s use of social care services in Scotland. In particular, we aim to compare this use to individual’s diagnosed with other cancers and to those without a cancer diagnosis.